2005
DOI: 10.1038/sj.onc.1209136
|View full text |Cite
|
Sign up to set email alerts
|

AML1 deletion in adult mice causes splenomegaly and lymphomas

Abstract: AML1 (RUNX1) encodes a DNA-binding subunit of the CBF transcription factor family and is required for the establishment of definitive hematopoiesis. AML1 is one of the most frequently mutated genes associated with human acute leukemia, suggesting that genetic alterations of the gene contribute to leukemogenesis. Here, we report the analysis of mice carrying conditional AML1 knockout alleles that were inactivated using the Cre/loxP system. AML1 was deleted in adult mice by inducing Cre activity to replicate AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
116
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 45 publications
(44 reference statements)
8
116
2
Order By: Relevance
“…Their central role in orchestrating proper differentiation of hematopoietic stem cells is underscored by the ablation of definitive hematopoiesis in Runx1 or Pebp2b Ϫ/Ϫ knockout mice [4][5][6] and an expanded HSC compartment in conditional Runx1-deficient mice. [7][8][9][10] However, although the overall biologic functions of RUNX1 are becoming clear, how these functions are controlled at the molecular level and the contribution of PEBP2-␤ remain to be fully determined.The evolutionarily conserved partner protein PEBP2-␤ is known to enhance DNA binding ability of all 3 mammalian RUNX proteins (RUNX1-3) by inducing allosteric change of DNA binding Runt domain without direct DNA contact. In addition, we have previously reported that PEBP2-␤ regulates RUNX1 metabolic stability by preventing its ubiquitin-mediated degradation.…”
mentioning
confidence: 99%
“…Their central role in orchestrating proper differentiation of hematopoietic stem cells is underscored by the ablation of definitive hematopoiesis in Runx1 or Pebp2b Ϫ/Ϫ knockout mice [4][5][6] and an expanded HSC compartment in conditional Runx1-deficient mice. [7][8][9][10] However, although the overall biologic functions of RUNX1 are becoming clear, how these functions are controlled at the molecular level and the contribution of PEBP2-␤ remain to be fully determined.The evolutionarily conserved partner protein PEBP2-␤ is known to enhance DNA binding ability of all 3 mammalian RUNX proteins (RUNX1-3) by inducing allosteric change of DNA binding Runt domain without direct DNA contact. In addition, we have previously reported that PEBP2-␤ regulates RUNX1 metabolic stability by preventing its ubiquitin-mediated degradation.…”
mentioning
confidence: 99%
“…33 In recently published mouse studies, it was shown that deletion of AML1, transgenic expression of EVI1 or NUP98-HOXD13, as well targeting of Dido lead to the development of a hematopathological picture similar to human MDS or MD/MPS. [20][21][22][23] These recent studies have provided key information on the molecular basis of MDSFin particular, how selected genetic abnormalities may lead to defects in proliferation and differentiation and to leukemic transformation in MDS and MD/MPS. [20][21][22][23] Our model of radiation-induced MDS may be particularly suited for the study of the therapeutic value of alloHSCT and DLI.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of genetically engineered mouse models of MDS exists, and these were developed with the objective of unraveling the molecular etiology and pathogenesis of MDS. [20][21][22][23] Here, we describe a radiation-induced model of MD/MPS in mice, which, in addition, is suitable for the study of allograft-mediated immune effects. Using this model, we were able to experimentally demonstrate that MD/MPS is susceptible to DLI in the context of MHC-mismatched alloBMT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations